Choosing to choose or not - Roy Shoval; Noam Karsh; Baruch Eitam (Judgment and Decision Making, 2022)
To what degree do people prefer to choose for themselves and what drives this preference? Is it memory-based and results from a life-long association between choices and better outcomes, or is the process of choice itself reinforcing? In a new paradigm, across 6 experiments, participants experienced both ’Own Choice’ and ’Computer Picks’ conditions with identical outcomes before selecting which condition to re-experience in the final part of the experiment. Consistent with previous work, an overwhelming majority ( 83%) preferred own-choice. Several variations of the paradigm reveal that (1) Preference For Choice (PFC) is reduced when thinking about the task without actually choosing in it, (2) PFC is substantially reduced by choice-unrelated cognitive load, and (3) Preference For Choice is further diminished when selection is based on criteria other than one’s preferences. Across experiments, participants’ self-rated enjoyment predicted a significant portion of their PFC, while their perceived gains had little to no predictive value. If PFC stems solely from past reinforcement learning (i.e., memory) then neither performing another few scores of choices nor adding cognitive load to that sequence of choices would be expected to dramatically affect it. Hence, our findings suggest that a significant part of this preference stems from the process of choice itself, and that the experience it confers can itself be reinforcing. We discuss the implications of the proposed mechanism for PFC, which leads us to the prediction that PFC may be muted or even reversed under specific conditions and what this means for when the ‘opposite’ effect – sticking with the default – will occur.